Revision of the genus Oenopia Mulsant, 1850 (Coleoptera: Coccinellidae) from China - Wang, Zi-Zhao; Zhu, Zi-Hao; Jin, Ming-Xiao; Wang, Xing-Min (Zootaxa, 2026)
The genus Oenopia Mulsant, 1850 from China is reviewed, including 33 species. Five new species are described, namely Oenopia latitegmina Wang & Wang sp. nov., Oenopia sanxiaensis Wang & Wang sp. nov., Oenopia stylifera Wang & Wang sp. nov., Oenopia tianquanensis Wang, Jin & Wang sp. nov. and Oenopia transversifasciata Wang & Wang sp. nov.. Oenopia adelgivora Poorani, 2002, Oenopia excellens (Crotch, 1874) and Oenopia smetanai Canepari, 1997 are recorded from China for the first time. Based on examined specimens and literature records O. medogensis (Jing, 1987) is returned to Xanthadalia Crotch. The taxonomic status of Oenopia yadongensis is discussed and remains questionable. Detailed images of external and genital characters or revised species, and descriptions of new species are presented. A key to species of the genus Oenopia from China is also given.